Islamic Liberalism and Beyond - Parvez Manzoor (International Institute of Islamic Thought, 1990)
Islamic Liberalism and Beyond Parvez Manzoor The logic of faith is truth: it proclaims a paradigmatic order of reality. The logic of the world is power: it promotes a pragmatic view of things. The logic of Islam is to conjoin the paradigmatic truth of faith with the pragmatic order of the Community. Holding fast to the transcendence of Truth, Islam does not, as it were, allow the world to slip out of its hands. For the existence of its faith transcendence and immanence are as essential as exhaling and inhaling. Of course, by renoucing the "either/or" option, Islamic tradition gets entangled in a number of moral and metaphysical paradoxes: its secular public order gets confounded with the transcendent realm of faith and the historical community emerges as the supreme value of Islam. And yet, despite the identity of 'Islamic reason' and raison d'etat in the sacrosanct discourse of the fuqaha; the dominant ethos of Islamic civilization has been apolitical, nay downright antipolitical. Even the most ardent champions of the 'inerrancy' of the Community have upheld the sovereignty of the paradigmatic and renounced all pretenceof the pragmatic. The absolute verity of a transcendent Revelation, they have argued with unyielding logic, requisitions no authentication from the contingent praxis of an immanent Community. The truth of Islam, sublime, transcendant and unassailable, cannot suffer any humiliation on account of the existential infirmity of sinful Muslims. Islam stands in need of no validation save its own self-validation. Doubtless, this reckless and imperious transcendentalism of tradition has had catastrophic consequences for the Muslim polity. The paradigmatic logic of faith has successfully prevented Muslim consciousness from perceiving any pragmatic order of reality as 'Islamic'. Indeed, perverting the argument for transcendence into a pretext for abdicating history, Muslims have been guilty of practising the kind of pernicious dichotomy of faith and community that they have vehemently described in theory. The doctrinal quest for Islamic legitimacy has been instrumental in devalourizing the historic Community and its existential testimony. Theory and practice, in other words, have come to dwell in separate spheres in the civilization of Islam. Indeed, every assertion to the contrary, the Muslim Ummah of history is not a power-polity, not a ...